Optimization of extraction conditions and evaluation of Manilkara zapota (L.) P. Royen fruit peel extract for in vitro α-glucosidase enzyme inhibition and free radical scavenging potential - Pravin P. Karle; Shashikant C. Dhawale; Vijay V. Navghare; Shivraj S. Shivpuje (SpringerOpen, 2021)
Abstract Background Most of the edible portions like peel and skin of some fruits is discarded while consuming it, though they are rich in several health beneficial phytochemicals or nutrients. Many reports from literature are about fruit pulp of (Sapota) Manilkara zapota (L) P. Royen having high radical scavenging and antioxidant potential, but the studies relating to peel extracts are scanty. Regardless of its commendable phytoconstituents which could have free radical scavenging potential, this fruit peel is as yet still needed to be assessed for in vitro antidiabetic prospects. Hence, the present study aims at evaluating in vitro free radical scavenging and α-glucosidase enzyme hindrance abilities of this fruit peel. Results With a maximum considerable % extractive yield (18.90%) in 70% ethanol, this study has demonstrated that 70% ethanolic extract of Manilkara Zapota (L.) P. Royen Fruit Peel (MZFP) has the highest in vitro free radical scavenging potential as compared to extracts of other solvents viz. n-hexane, chloroform, acetone, absolute ethanol, and water by DPPH and H2O2 assays. In order to optimize the extraction condition parameters, MZFP sample evaluated with three different concentrations of ethanol (40%, 70%, 100%), extraction times (6 h, 9 h, 12 h), and temperatures (40 °C, 50 °C, 60 °C) to get the highest radical scavenging potential. The MZFP when extracted with 70% ethanol, at 50 °C for 12 h, showed higher DPPH (IC50 = 0.34 and 88.42% inhibition at 1 mg/ml) and H2O2 (IC50 = 32.69 and 65.78% inhibition at 50 μg/ml) radical scavenging potential than absolute and 40% ethanolic extracts, when ascorbic acid was used as a reference standard. While further evaluation for in vitro α-glucosidase enzyme inhibition, 70% ethanolic MZFP extract demonstrated high inhibition activity (IC50 = 104.23 ± 1.75 μg/ml) than absolute ethanolic extract (IC50 = 111.65 ± 1.57 μg/ml) with a significant difference (p < 0.05), when acarbose was taken as reference inhibitor (IC50 = 86.93 ± 0.74 μg/ml). Conclusions Overall results indicated that MZFP 70% ethanolic extract exhibited promising in vitro radical scavenging and α-glucosidase enzyme inhibition potential. Thus, suggesting further studies with isolated phytochemicals from peel to explore its potentials for antidiabetic activity through in vitro α-glucosidase enzyme inhibition.